The risk of impending preterm delivery in asymptomatic patients with a nonmeasurable cervical length in the second trimester - Vaisbuch, Edi; Romero, Roberto; Mazaki-Tovi, Shali; Erez, Offer; Kusanovic, Juan Pedro; Mittal, Pooja; Gotsch, Francesca; Ward, Clara; Romero, Vivian; Chaiworapongsa, Tinnakorn; Pacora, Percy; Yeo, Lami; et al. (American journal of obstetrics and gynecology, 2010)
The purpose of this study was to determine the pregnancy outcome of asymptomatic patients in the second trimester with a nonmeasurable cervical length (0 mm). This retrospective cohort study included 78 patients with singleton pregnancies and a sonographic nonmeasurable cervix that was detected at 14-28 weeks of gestation. Patients with cervical cerclage were excluded. We found that (1) 75.3% of the patients delivered before 32 weeks of gestation; (2) the median diagnosis-to-delivery interval was 20.5 days, and the delivery rate within 7 and 14 days was 28.2% and 35.6%, respectively; and (3) patients with a nonmeasurable cervix that was diagnosed at <24 weeks of gestation had a shorter median diagnosis-to-delivery interval than patients who were diagnosed at 24-28 weeks of gestation (17.5 vs 41 days; P = .009). Asymptomatic women with a nonmeasurable cervix in the second trimester have a median diagnosis-to-delivery interval of approximately 3 weeks. Almost 65% of these patients will not deliver within 2 weeks, yet 75% of them will deliver before 32 weeks of gestation. The earlier a nonmeasurable cervix is identified, the shorter the diagnosis-to-delivery interval.